1998
DOI: 10.1002/hep.510280303
|View full text |Cite
|
Sign up to set email alerts
|

Increased cd1d expression on small bile duct epithelium and epithelioid granuloma in livers in primary biliary cirrhosis

Abstract: Cluster of differentiation 1 (CD1) is a family of four distinct nonpolymorphic major histocompatibility complex class I-like molecules that can present microbial nonpeptide lipid antigens to T cells. Among the CD1 gene family, CD1d is found in a wide range of tissues including the intestine and liver, and has been proposed to play an important role in mucosal immunity. Primary biliary cirrhosis (PBC) is an immune-mediated liver disease involving the intrahepatic small bile ducts, which also belong to the mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 30 publications
3
69
1
Order By: Relevance
“…80,84 CD1d is expressed at very low levels in healthy human as well as rodent hepatocytes, 7,30,31 but increases markedly on epithelioid granuloma cells in PBC. 81 CD1d is expressed on cholangiocytes and epithelial cells of the small bile ducts in earlier stage PBC and is lost in the late stages. A subsequent study demonstrated that CD3 ϩ /CD57 ϩ cells are increased in the portal tracts, in particular around the interlobular bile ducts, in patients with PBC.…”
Section: Role In Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…80,84 CD1d is expressed at very low levels in healthy human as well as rodent hepatocytes, 7,30,31 but increases markedly on epithelioid granuloma cells in PBC. 81 CD1d is expressed on cholangiocytes and epithelial cells of the small bile ducts in earlier stage PBC and is lost in the late stages. A subsequent study demonstrated that CD3 ϩ /CD57 ϩ cells are increased in the portal tracts, in particular around the interlobular bile ducts, in patients with PBC.…”
Section: Role In Liver Diseasementioning
confidence: 99%
“…Focal CD1d staining was increased on cholangiocytes and inflammatory cells in chronic HCV infection, 56 as previously described in PBC. 80,81 Furthermore, nonclassical variant CD1d-reactive T cells were found in uninfected livers, although they were found more frequently in HCV-infected donors. Although CD1d-reactive T cells from mild cases had a strong Th1 bias, Th2 cytokines were also produced in advanced fibrosis and cirrhosis.…”
Section: Role In Infections Of the Livermentioning
confidence: 99%
“…Previous studies described the profiles of inflammatory cells surrounding bile ducts in PBC (9,(14)(15)(16)(17). Cellular profiles may change depending on the process of biliary inflammation.…”
Section: Immunopathological Characteristics Of Damaged Biliary Epithementioning
confidence: 99%
“…Recent studies have demonstrated that CD1d1 expression is up-regulated in response to some infections or inflammatory conditions. For example, increased CD1d1 expression can be detected on mucosal-associated B cells after the development of intestinal inflammation (30) and on biliary hepatocytes during hepatitis C virus infection (31). These findings suggest that the levels and cell type-specific expression of CD1d1 may affect the functions of iNKT cells.…”
mentioning
confidence: 92%